IMPROVING GROWTH PATTERN OF INDIAN MAJOR CARPS THROUGH ORGANIC CULTURE SYSTEM - GOSWAMI, B.; NAYAK, A.; MAITY, T. (Journal of the Inland Fisheries Society of India, 2026)
The purpose of the present study was to assess and compare the growth pattern of Indian Major Carps mainly catla (Labeo catla), rohu (Labeo rohita), and mrigal (Cirrhinus mrigala)  which was carried out in twenty one (21) earthen ponds, each covering an area of 0.133 hectares, over duration of 280 days. The stocking density of fish seeds were @ ten thousands (10,000 nos.) fingerlings per hectare as an equal numbers under three different culture systems: Normal Culture System (NCS), Conventional Culture System (CCS), and Organic Culture System (OCS). The NCS used cow dung as a fertilizer without involving supplementary feeding or aeration. In the CCS, a commercial fish feed, organic and inorganic fertilizers were used without aeration. The OCS depended on mainly use of organic fertilizers and organic fish feed except aeration. To ensure consistency of each farming practices was made replica of three. In the NCS and CCS, the experimental ponds were fertilized with cow dung @15,450 kg ha-1, urea @ 31 kg ha-1, and triple super phosphate (TSP) at 16 kg ha-1. For the OCS, fertilization involved vermin-compost @ 12,443 kg ha-1 and vermin-wash @ 93.33 l ha-1. Fertilizers were applied before one week of stocking and also fertilized with the same quantities every two weeks throughout the culture period. The NCS operated without any supplementary feed. In contrast, the CCS employed a commercial pelleted feed (2-4 mm in dia) containing 32% crude protein produced locally, with key ingredients such as wheat flour, mustard oil cake, fish meal, soybean meal, vitamins and minerals.  In the OCS, organic fish feed was used which contains 32% crude protein and made with earthworm meal, maize meal, and soybean meal. Feeding was adapted to cater to surface, column, and bottom feeders by suspending the feed using nylon ropes and bags at different depths (0.7 m, 1.0 m, and 1.13 m). Feeding was not applied during sampling or rainy days, and supplemented feed was provided twice daily in both CCS and OCS experimental ponds at decreasing rates based on fish biomass over the study period. The results illustrated that the survival rate of Indian Major Carps were consistent across all three culture systems. However, the Organic Culture System (OCS) showed significantly better outcomes in terms of feed conversion ratio (FCR), specific growth rate (SGR) and total fish production compared to the Normal and traditional. Furthermore, water quality in the OCS remained within optimal ranges throughout the culture period. This study reveals that using an organic culture system in fish farming not only enhances the fish production efficiency but also maintains superior water quality over time.